A construção de um instrumento de avaliação da proficiência oral do professor de língua estrangeira - Consolo, Douglas Altamiro (UNICAMP. Programa de Pós-Graduação em Linguística Aplicada do Instituto de Estudos da Linguagem (IEL), 2004)
This article presents a theoretical background and some results from a research project that aimed at investigating the issue of EFL teacher's oral language proficiency (OLP-EFLT) in contexts of English Language and Literature undergraduate courses (Licenciatura em Letras, henceforth Letter courses) in Brazil.The project analyses OLP-EFLT from the perspective of students' and teachers' views and expectations about OLP in English and by means of a language test.The Test of Oral Proficiency English, labelled as TEPOLI (Teste de Proficiência Oral em Língua Inglesa), designed as a research instrument, was taken by graduating students from three Letters courses in two consecutive years. The data presented here derive from results and transcripts of TEPOLI concerning one of the contexts investigated. Such results contribute for a definition of the characteristics of OLP-EFLT, especially among graduating students of Letters, and the design of an oral test to assess their OLP. However, the investigation indicates the needs for further research on linguistic aspects and oral tasks that are more representative of OLP-EFLT. The theoretical and methodological aspects dealt with here may nevertheless motivate future work in the issue of teachers' language proficiency and how to make valid and reliable claims about OLP-EFLT.
Keywords: testing; oral proficiency; linguistic and communicative competence